Generalized 2-D continuous-discrete linear systems with delays - Kaczorek, Tadeusz (1932- ) (Zielona Góra: Uniwersytet Zielonogórski)
A general Kurek (K) type model and a general Roesser (R) type model of 2-D continuous-discrete linear systems with deviating arguments are introduced. A solu tion and the general response formula for the regular general type model of 2-D continuous-discrete linear systems with delays are derived. The necessary and sufficient conditions for the local reachability and the local controllability of the regular general K type model are established. The minimum energy control of the regular model is solved.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka